Routing architecture optimizations for high-density embedded programmable IP cores. - Hallschmid, P. (IEEE Transactions on VLSI systems)
Programmable logic cores differ from stand-alone field-programmable gate arrays in that they can take on a variety of shapes and sizes. With this in mind, we investigate the detailed routing architecture of rectangular programmable logic cores. We quantify the effects of having different X and Y channel capacities and show that the optimum ratio between the X and Y channel widths for a rectangular core is between 1.2 and 1.5. We also present a new switch block family optimized for rectangular cores. Further, we quantify the effects of logic block pin placement. Compared with a simple extension of an existing switch block, our new architecture leads to a density improvement of up to 11.9%. Finally, we show that, if the channel width, switch block, and pin placement are chosen carefully, then the penalty for using a rectangular core (compared to a square core with the same logic capacity) is small; for a core with an aspect ratio of 2:1, the area penalty is 1.6% and the speed penalty is 3.8%.